Hemostatic Resuscitation in Postpartum Hemorrhage—A Supplement to Surgery. Issue 2 (June 2016) - Ekelund, K.; Hanke, G.; Stensballe, J.; Wikkelsøe, A.; Albrechtsen, C.K.; Afshari, A.
Abstract : ( Acta Obstet Gynecol Scand . 2015;94:680–692) Although postpartum hemorrhage is preventable, it remains a highly prevalent cause of maternal death in poorer countries and seems to be increasingly common in higher income countries as well. Although surgical options can be the most beneficial course of treatment, these measures may fail to stop the hemorrhage. The use of uterotonic agents, controlled cord traction, uterine massage, intrauterine balloon tamponade, or uterine artery embolization can also prove ineffective when health care professionals are faced with a persistent hemorrhage. It is therefore important to determine effective and affordable treatments that can be used in addition to surgical options and uterotonic agents to ensure that hemostasis is achieved. The authors of this review examined the existing literature to evaluate other supplemental methods that are currently used to treat postpartum hemorrhage.